Research of the Chinese Project of Creation the Silk Road Economic Belt - Y. V. Kosov; A. D. Shmatko (Евразийская интеграция: экономика, право, политика, 2019)
In the article, the retrospective analysis of the Silk way as multimain cross-border project in a historical context and in modern economic conditions is made. Within the project of «The Silk Road Economic Belt», creation of three transeuroasian economic corridors is considered: northern (China - Central Asia - Russia - Europe), central (China - Central and Western Asia - the Persian Gulf and the Mediterranean Sea) and southern (China - Southeast Asia - the Southern Asia - the Indian Ocean). Positive effects from participation in this project of the Russian Federation, includ ing due to economic development of border regions are characterized.